Aboriginal and Torres Strait Islander health checks: sociodemographic characteristics and cardiovascular risk factors - Danielle C Butler; Jason Agostino; Ellie Paige; Rosemary J Korda; Kirsty A Douglas; Vicki Wade; Emily Banks (Sax Institute, 2022)
Objective: To quantify Aboriginal and Torres Strait Islander health check claims in Australian adults in relation to sociodemographic and health characteristics, including prior cardiovascular disease (CVD) and CVD risk factors. Methods: The study involved analysis of baseline data (2006-2009) from the Sax Institute's 45 and Up Study, involving 1753 Aboriginal and Torres Strait Islander adults in New South Wales, Australia, linked to Medicare Benefits Schedule (MBS) hospital and death data (to December 2015). The outcome was a claim for receiving a Medicare-funded Health Assessment for Aboriginal and Torres Strait Islander People (MBS item 715) in the 2 years before December 2015. Logistic regression was used to estimate odds ratios (ORs) for receiving a health check in relation to sociodemographic and health characteristics. Results: One-third (32%) of participants received at least one Medicare-funded health check in the 2-year period. The probability of receiving a health check was higher for women than men (adjusted OR 1.47; 95% CI 1.18, 1.84), for those with lowest education than for those with highest education (OR 1.58; CI 1.11, 2.24), for those in a regional area (OR 1.56; CI 1.22, 2.01) or remote area (OR 2.38; CI 1.8, 3.16) than for those in major cities, for those with prior CVD than for those without (OR 1.80; CI 1.42, 2.27), for those with CVD risk factors than for those without (adjusted OR between 1.28 and 2.28, depending on risk factor), for those with poor self-rated health than for those with excellent self-rated health (OR 3.15; CI 1.76, 6.65) and for those with more than 10 visits to a general practitioner (GP) per year than for those with 0-2 visits (OR 33.62; CI 13.45, 84.02). Additional adjustment for number of GP visits or self-rated health substantially attenuated ORs for prior CVD and most CVD risk factors. When mutually adjusted, use of GP services and poorer self-rated health remained strongly associated with receiving a health check. Conclusions: Aboriginal and Torres Strait Islander people with the greatest healthcare need and at highest risk of CVD were more likely to receive a health check; however, a significant proportion of those who were eligible had not received this preventive care intervention. Findings indicate that there is greater potential for the use of health checks (MBS item 715) in improving identification and management of Aboriginal and Torres Strait Islander people at high risk of CVD, potentially preventing future CVD events.